Review of conservation policies for wildlife protection (Zoological Records and Reviews, 2024)
Effective wildlife conservation depends fundamentally on the quality, coherence, and implementation of conservationpolicies at local, national, and international scales. Europe's multilevel conservation policy architecture -- encompassingthe EU Habitats Directive, Birds Directive, CITES, the Bern Convention, and national species action plans -- representsone of the most comprehensive regulatory frameworks for wildlife protection globally, yet persistent implementation gaps,funding shortfalls, and cross-border coordination failures continue to undermine conservation outcomes for many priorityspecies. This review synthesises evidence from 186 primary studies (2005-2024) examining the effectiveness,compliance, and policy design features of wildlife conservation frameworks in European contexts. Policy effectivenesswas evaluated across five dimensions: legal stringency, implementation consistency, enforcement capacity, adaptivemanagement provisions, and cross-border coordination mechanisms. The EU Habitats Directive's Article 17 reportingcycle -- assessing favourable conservation status for Annex II species every six years -- provides the most systematicpan-European evidence base for policy outcome evaluation, with the most recent 2019 assessment reporting only 15%of assessed species in favourable status. Key policy design features associated with improved conservation outcomesinclude: species-specific action plans with quantified targets, dedicated funding mechanisms, independent monitoring,and transboundary management agreements. Emerging policy instruments -- biodiversity net gain requirements,payment for ecosystem services, and the EU Nature Restoration Law -- are evaluated for their potential to addresspersistent implementation gaps. A framework for evidence-based wildlife policy evaluation and reform is presented.